CAMPUR KODE YANG DIGUNAKAN DALAM ACARA TALK SHOW KICK ANDY DI METRO TV - Usemahu, Ariel; Pamantung, Rina P.; Lasut, Theresia M.C (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2022)
Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â ABSTRACTÂ  Â  Â The tittle of this skripsi is â€œCampur Kode yang Digunakan dalam Acara Talk Show Kick Andy di Metro TVâ€. It is analyzed from the sociolinguistic point of view. The aims of this research are to identify, classify, and analyze the code-mixing used by the host, Andy F. Noya, and his guest stars in the program â€œKick Andyâ€ (Talk show program on Metro TV). The research uses qualitative descriptive approach, by using the theory of Hoffman (1991:112) and Kim (2006: 43). The data were collected from utterances containing code-mixing in English by Andy F. Noya and the guest stars, in video / 14 episodes. The total number of code-mixing found are 120 by Andy F. Noya and guest stars in â€œKick Andyâ€ talk show program on Metro TV. The results of this research show that two types of code-mixing found are intra sentential code-mixing and intra lexical code-mixing. While the type of involving a change of pronunciation is not found in the data. The results of this research also show that there are 5 of 6 factors that cause people to do code-mixing in â€œKick Andyâ€ talk show program on Metro TV, namely bilingualism, speaker and partner speaking, social community, situation, and vocabulary. However, the factor of prestige is not found in the data.Keywords: Code-Mixing, â€œKick Andyâ€ talk show program, Sociolinguistics.